Assessment of willingness to pay for improved air quality using contingent valuation method - S. Akhtar; W. Saleem; V.M. Nadeem; I. Shahid; A. Ikram (Global Journal of Environmental Science and Management)
Rapid urbanization and severe air quality deterioration in Pakistan have increased citizens’s concern towards air pollution. This study, conducted in November, 2016, aimed to develop relationship between degraded air quality and resident’s willingness to pay for improved air quality in city of Lahore, Pakistan through contingent valuation method to quantify an individual’s willingness to pay for improved air quality. Hypothetical market was created and 250 respondents, selected through random sampling, were asked to respond to pre tested questionnaire. Results revealed that 92.5% of respondents showed positive willingness to pay and average predicted willingness to pay by each person was $9.86 per month. Respondents were willing to pay $118 per year which was 1.27% of their mean monthly income. Stepwise regression model was used to develop relationship between independent variables and willingness to pay. Most parameters accompanied by econometric analysis elaborated expected results. Results disclosed that annual household income, symptoms of respiratory diseases and self observed air pollution pointedly impact willingness to pay. It is concluded that despite of the fact that Pakistan is among the lower income countries with no rigid budget allocation for improvement in air quality, people of Pakistan are willing to pay to reduce air pollution load. One of the factor which effected the positivity of willingness to pay is that, a quite large number of people were suffering from pollution related respiratory disorders like asthma, chronic bronchitis, wheezing, cough, and chest congestion. Only 7.5% of respondents were not interested to pay for improved air quality which reported unconcerned attitude and lack of environmental awareness.